The role of members of the educational body in developing and modernizing the higher education system in the Syrian Arab Republic )The universities of Damascus and Catherine model( - Hassan, Maysoon Hassan (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The members of the educational body are one of the main pillars in the higher education system in the Arab Republic for their effective contribution to developing and modernizing the educational process and their importance in human development. The role of members of the educational body is to develop higher education by implementing their university policy, mapping the future features of their college, and contributing to the rise of their country And achieving the goals of the university, reconciling the contents of the subject they are studying with the needs of society and students, and following the mechanisms of guidance and guidance for students, developing teaching tasks assigned to them, contributing to achieving quality in higher education, preparing Alba Thane to raise the scientific, educational, cultural and professional productivity based on the reality of the reform process requirements in higher education. The research aims to identify the role of members of the educational body in the universities of Damascus and Tishreen in the development and modernization of the higher education system in the Syrian Arab Republic, and to reveal the differences between members of the educational body in both the universities of Damascus and Tishreen and their role in developing higher education according to the variable of the academic rank. After studying and analyzing, the research reached the following results: There are statistically significant differences between the averages of the members of the educational staff in their role to develop higher education according to the variable of the academic rank. There are statistically significant differences between the averages of the educational staff members ’scores in building curricula and university curricula according to the variable of the academic rank. There are statistically significant differences between the averages of the members of the educational body in their role to develop the educational process and renew its methods according to the variable of the academic rank. One of the research proposals is the participation of workers in their different sectors in higher education institutions by setting the educational strategy and policy for these institutions يُعد أعضاء الهيئة التعليمية إحدى الركائز الأساسية في منظومة التعليم العالي في الجمهورية العربية لمساهمتهم الفعَّالة في تطوير العملية التعليمية وتحديثها ولأهميتهم في التنمية البشرية, فدور أعضاء الهيئة التعليمية يتمثل في تطوير التعليم العالي من خلال تنفيذ سياسة جامعتهم, ورسم ملامح المستقبل لكليتهم, والإسهام في نهضة وطنهم وتحقيق أهداف الجامعة, والتوفيق بين محتويات المادة التي يدرسونها وحاجات المجتمع والطلبة, واتباع آليات الإرشاد والتوجيه للطلبة, وتطوير المهام التدريسية الموكلة إليهم, والمساهمة في تحقيق الجودة في التعليم العالي, وإعداد الباحثين من إجل رفع الإنتاجّية العلميّة والتربوية والثقافيّة والمهنيّة المبنيّة على واقع متطلبات عملية الإصلاح في التعليم العالي. يهدف البحث إل التعرف على دور أعضاء الهيئة التعليمية في جامعتي دمشق وتشرين في تطوير وتحديث منظومة التعليم العالي في الجمهورية العربية السورية، والكشف عن الفروق بين أعضاء الهيئة التعليمية في كل من جامعتي دمشق وتشرين ودورهم في تطوير التعليم العالي تبعاً لمتغير المرتبة العلمية. وبعد الدراسة والتحليل توصل البحث إلى النتائج الآتية: 1- توجد فروق ذات دلالة إحصائية بين متوسطات درجات أعضاء الهيئة التعليمية في دورهم لتطوير التعليم العالي تبعاً لمتغير المرتبة العلمية. 2- توجد فروق ذات دلالة إحصائية بين متوسطات درجات أعضاء الهيئة التعليمية في بناء المناهج والمقررات الدراسية الجامعية تبعاً لمتغير المرتبة العلمية. 3- توجد فروق ذات دلالة إحصائية بين متوسطات درجات أعضاء الهيئة التعليمية في دورهم لتطوير العملية التعليمية وتجديد أساليبها تبعاً لمتغير المرتبة العلمية. 4- من مقترحات البحث مشاركة العاملين في شرائحهم المختلفة في مؤسسات التعليم العالي بوضع الاستراتيجية والسياسة التربوية لتلك المؤسسات